Airway reconstruction surgical dissection manual - Propst, Evan J. (Plural Publishing, 2014)
Otolaryngology--head and neck surgeons, general surgeons, and thoracic surgeons are required to know how to perform various types of open airway surgery. However, due to a decrease in the number of patients with subglottic or tracheal stenosis and resident work hour restrictions, exposure to these cases during training is often inadequate. As a result, there is an ever-increasing need for training programs to develop lifelike open airway simulation models. These in turn will promote competency-based surgical residency training and a drive toward continuing medical education and maintenance of.